Thermal Transport and Thermoelectric Properties of Rb2PdX6 (X=Cl, Br) from First‐principles Study. Issue 2 (2nd December 2022) - Liu, Rongkun; Hu, Yanxiao; Feng, Chunbao; Ding, Guangqian; Zhang, Gang; Li, Dengfeng
Abstract: Vacancy‐ordered double perovskites are characterized by stable structure, non‐toxicity, low thermal conductivity, and large Seebeck coefficient, which are potential thermoelectric materials. In this work, the thermal transport and thermoelectric properties of Rb2 PdX6 (X=Cl, Br) are theoretically investigated. We find that the calculated thermal conductivity is underestimated from the phonon Boltzmann transport equation (PBTE) since the mean free path of a large number of phonons is less than the Ioffe‐Regel limit. The room‐temperature thermal conductivities of Rb2 PdCl6 and Rb2 PdBr6 are 0.42 W m −1 K −1 and 0.22 W m −1 K −1 based on two‐channel phonon transport mode, respectively. The thermal conductivity of Rb2 PdBr6 is almost unchanged with the temperature. Rb2 PdX6 (X=Cl, Br) have large Seebeck coefficient for p‐type doping due to triple degeneracy in the VBM and the thermoelectric property of p‐type doping is better than that for n‐type doping. The ab initio scattering and transport program (AMSET) is used to calculate the electron scattering rate. At 700 K, the maximum ZT of p‐type doping Rb2 PdCl6 and Rb2 PdBr6 can reach to 0.51 and 1.31, respectively. Replacement of Cl by Br results in lower thermal conductivity and smaller bandgap, and thus larger the maximum ZT value. This work demonstrates that Rb2 PdBr6 is a potential high‐performance p‐type thermoelectric perovskite material. Abstract : The thermal transport and thermoelectric properties of Rb2 PdX6 (X=Cl, Br) are theoretically investigated. The diffuson‐like phonons have large contribution to the thermal transport of them. Rb2 PdX6 (X=Cl, Br) have large Seebeck coefficient for p‐type doping due to triple degeneracy in the valence band edge and the thermoelectric property of p‐type doping is better than that of n‐type counterpart. At 700 K, the maximum ZT of p‐type Rb2 PdCl6 and Rb2 PdBr6 are 0.51 and 1.31, respectively. Rb2 PdBr6 is a high‐performance p‐type thermoelectric perovskite material.